Divorce italian style: on the concepts of place and history in a work of Ignazio Gardella - Pierini, Orsina Simona (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
The article deals with the complex relationship between place and history, through the interpretation of an important example of one of the masters of Italian post-war architecture, Ignazio Gardella. These two terms, place and history, have often been seen in the theories of architectural design, in particular Italian, as an established couple, from which to obtain excellent results with security. In fact the two terms are often in opposition: in this essay will explore the character of the one and the other, their specific differences, and especially their apparent contradictions. The long history of the project by Ignazio Gardella for the Faculty of Architecture of Genoa and the complexity of the place on which is settled make it a prime example to investigate the operation of concepts often evoked in an abstract way as fundamentals of the architectural project.
Keywords: Architectural discipline; modern architecture; poetics; present; Genoa